HYDROMAGNETIC STABILITY OF STREAMING COMPRESSIBLE CYLINDER PERVADED BY MAGNETIC FIELD - L. Azwz, Shimaa (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The Stability of MHD compressible streaming fluid cylinder of radius endowed with surface tension and pervaded by axial magnetic field has been developed. The stability criterion is established in general form. The model is capillary unstable only in the axisymmetric mode m=0, the electromagnetic forces acting interior and exterior the fluid cylinder are stabilizing and the MHD stability is destabilizing for small wave length. In the latter case the instability shrinks with increasing the magnetic intensity. However the compressibility has a stabilizing tendency.